CAREER DEVELOPMENT POTENTIAL FROM LANNA WISDOM HERBAL PRODUCTS OF THE ELDERLY IN JAW YONG HERB CLUB PA TAN TEMPLE BUAK KHANG SUBDISTRICT SAN KAMPHAENG DISTRICT CHIANG MAI PROVINCE - Sanamphol , Acharaporn; Lunsomlong, Narongsak; larping, Uten; ., Phrasutthisanmethi Chaiyan; Lunsomlong, Narongsak; Wanta, Purawich (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to 1) study the occupational context from Lanna herbal products of the elderly in Chiang Mai; 2) develop professional potential from herbal products. It is a mixed research method. qualitative research the key informants used a specific sample selection method, namely the chairman of the Jaoyoung Herbal Club. The abbot of Wat Pa Tan and the monks, working groups and leaders of the elderly at Wat Pa Tan were 19 monk/person and quantitatively researched the total population of 180 figures/person. The sample group was the Wat Pa Tan Community Elderly School. The random sampling method was therefore a sample of 124 monk/person. The research result finds that 1) The elderly was mostly female, aged 60 years and over with primary education. occupation in agriculture and on the issue of professional potential development from herbal products, Lanna wisdom of the elderly, resulting in the elderly income from products Most of which are supported by private networks, temples, community members. and from the government respectively. 2) Occupational potential development from herbal products of Lanna wisdom of the elderly in Chiang Mai. It was found that the monks were the center of mind for the development of professional potential from herbal products together with community sages who have knowledge and experience in Thai traditional medicine to teach the elderly at the temple Therefore, the Jaoyoung Herbal Club was established with the elders working with the temple. And continue to develop and make more and more herbal products with the elderly to help There are network partners from volunteers. from the public and private sectors jointly develop potential the results that occur with the elderly are psychological outcomes. Elderly people are happy from participating in activities. The mind including generating income for the elderly.